Wet peroxide oxidation of phenol over Cu-ZSM-5 catalyst in a flow reactor. Kinetics and diffusion study; Chemical Engineering Journal; Vol. 277 - Taran O. P. Oksana Pavlovna; Zagoruiko A. N. Andrey Nikolaevich; Ayusheev A. B.; Yashnik S. A.; Prikhodko R. V.; Ismagilov Z. R.; Parmon V. N. (2015, 2015)
Title screen